Demokrasi Pendidikan dalam Implementasi Kurikulum Merdeka, Studi Kritis dalam Tinjauan Pedagogik - Silvia Nurwanci; Tatang Muhtar; Yusuf Tri Herlambang (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Democratic education exists to address the challenges of globalization in Indonesia. Changes in the educational landscape driven by globalization have encouraged innovation, especially through the introduction of the independent curriculum. This study aims to examine the role of educational democracy in implementing the independent curriculum, which prioritizes democratic values with the goal of fostering creative, critical, and productive individuals, thereby enhancing the pedagogical quality of education. The method used is a literature review, examining various sources such as books, journals, and relevant publications. The independent curriculum seeks to create an educational process based on the principles of freedom, independence, and equality, guiding individuals toward a better life. Democratic education encompasses not only procedures but also values that respect human dignity. Literature review results from several sources indicate that implementing democracy in education through the Independent Curriculum has a significant impact on improving the quality of education in Indonesia, where all students are provided with engaging learning experiences. The Independent Curriculum, moreover, emphasizes principles of freedom, independence, and equal rights, aligned with the spirit of high-quality democratic education and integrated with the use of technology in the process.